Techno-economic Analysis of Solar Water Pumping System for Irrigation in Nepal - Karki, Amrit; Lohani, Sunil Prasad (Kathmandu University Journal of Science, Engineering and Technology, 2020)
Solar Water Pumping System is a process where electricity is used to drive water pumps produced from solar PV. It makes solar PV a flexible device to be used in remote Terai-plane areas in the southern region and hilly regions of the country where grid connection is inaccessible. The geographical belt of Nepal is in a very good solar region having about 4 to 5 peak sun hours and more than 300 sunny days in a year. Over 22 percent of agricultural land in Nepal does not have access to irrigation round the year. However, the immediate challenges for mass dissemination of solar water pumping system is the capital cost of the system which is beyond the affordable range for small farmers and rural people. Moreover, perceived benefit analysis of investment on solar water pumping system for irrigation along with possible extension of grid seems essential for investment decision. This paper presents the techno-economic analysis of solar water pumping system based on the design, investment and yearly return from the crops per hectare of land that could be applied in remote Terai areas of Nepal. Result shows the discounted payback period of nine years, which is within the lifetime of the system. Other economic parameters for instance, benefit cost ratio of 1.6 and internal rate of return of 18.15 % mark favorable to invest for the system. In addition, the solar water pumping system is compared with grid-electric pumping system. The cost of a pumping system operated by grid electricity includes the cost of feasible grid extension. The grid extension length is calculated in view of permissible voltage constraint which was performed with software DIgSILENT PowerFactory. The results indicated that, up to four hectare of land, investment on solar water pumping system seems more economical than grid-electric water pumping system with grid extension for a kilometer.